The Brown Coal Geology of the Gippsland Basin - Bolger P. F; Holdgate G. R; Thompson B. R; Webster R. L (The Australasian Institute of Mining and Metallurgy, 1992)
The Gippsland Basin in south-eastern Australia has an area of approximately 46 000 sq km. It is one of the world's major coal and petroleum bearing basins, with most of the former occurring in the smaller one fifth on-shore part. The stratigraphy, structure and economic resources of the Tertiary sedimentary pile is now well known through extensive drilling for coal and petroleum. In contrast, the older Cretaceous sequences through their lesser economic importance are relatively less explored. The sedimentational history of the Gippsland Basin has largely followed along similar lines of development to the many other southern Australian basins since the Cretaceous break-up of Gondwanaland. However, the scale of accumulation of coal and hydrocarbon source rocks is unprecedented and differentiates this basin, for reasons less well understood, from the others. Large scale open cut brown coal mining since the late-1920s has been carried out in the western extremities of the basin, while vigorous extraction of some two thirds of Australian petroleum products taken place in the offshore part. Brown coal seam thicknesses and economically winnable reserves are huge and outrank most other brown coal basins of the world. Development of the resource currently meets the need for electricity generation throughout the State of Victoria, but other future developments such as conversion to oil, being investigated.